Exploring the Effects of a Spanish Vocabulary Intervention to Teach Words in Depth to Second-Grade Students in Chile. Issue 3 (4th May 2019) - Baker, Doris Luft; Azcarrága, Maribel Granada; Correa, María Pilar Pomes; Lepe-Martinez, Nancy; Smolkowski, Keith
Abstract: This study explores the effects of a Spanish vocabulary intervention on the literacy outcomes of students at risk for vocabulary difficulties in Chile. We screened 2nd-grade students ( N  = 84) with a standardized Spanish vocabulary measure. We then randomly assigned students who scored below the 40th percentile ( n  = 30) to an intervention or control group. The intervention group received small-group vocabulary instruction 3 times per week. The comparison group received instruction on the same words from the teacher in the whole group. Results indicated significant large effects of the intervention on student vocabulary knowledge of taught words at posttest ( g  = 1.60) and 4 months later ( g  = 0.92). Effects were nonsignificant, though moderate, for reading comprehension ( g  = 0.50). Students in the intervention group were able to articulate significantly more complex sentences using the target words than students in the comparison group. We discuss implications for practice.